Non-truth-conditional aspects of meaning and the level of LF. - Reed, Lisa A. (University of Ottawa (Canada), 1993)
In contrast to the majority of research previously done on Logical Form (LF), this thesis places equal emphasis on its syntactic and semantic properties. Adopting a literal view of May's (1985) characterization of LF as "the level of representation which interfaces the theories of linguistic form and interpretation", this thesis uses syntactic information available at this level to construct a version of model-theoretic interpretation which can capture certain semantic phenomena. In particular, this thesis develops the hypothesis, inspired by Turkish specificity facts noted in Enc (1987, 1991), that a dissociation of Case and Theta-role assignments, signalled at LF, is one means by which a grammar may encode conventional implicatures. The French causative and Raising constructions, two examples of which follow, are offered as evidence for this contention. $$\vbox{\halign{#\hfil&&#\hfil\cr (1)\qquad &Je \ l'ai fait manger sa soupe.\cr &I him-ACC have made to-eat his soup\cr &`I made him eat his soup.'\cr (2)\qquad &Jean, \ c'est cet homme l\`a-bas.\cr &Jean, he is that man there-low\cr &`Jean, he's that man over there.'\cr}}$$The constructions in (1) and (2) are argued to have an LF configuration in which the underlined argument receives its Theta-role from a predicate which does not assign it Case, thus meeting the structural description noted above. This thesis shows that these dissociations encode conventional implicatures: in (1), there is an implicature regarding the degree autonomy possessed by the embedded subject; in (2), there is an implicature regarding the aspectual nature of the interval of time at which the predicative sentence is true. These implications are captured by a model-theoretic semantic component which reads off the syntactic tree available at LF.
Keywords: Language, Linguistics.